2006
DOI: 10.1111/j.1365-2672.2006.02813.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Erwinia amylovora strains from different host plants using repetitive-sequences PCR analysis, and restriction fragment length polymorphism and short-sequence DNA repeats of plasmid pEA29

Abstract: Aims:  The three main aims of the study were the assessment of the genetic relationship between a deviating Erwinia amylovora strain isolated from Amelanchier sp. (Maloideae) grown in Canada and other strains from Maloideae and Rosoideae, the investigation of the variability of the PstI fragment of the pEA29 plasmid using restriction fragment length polymorphism (RFLP) analysis and the determination of the number of short‐sequence DNA repeats (SSR) by DNA sequence analysis in representative strains. Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…Long-distance dispersal occurs principally via infected plant host material, limiting the number of invasion events into new regions. E. amylovora, even strains from the area of origin in North America (42), has been considered a genetically low-diversity species based on previous molecular approaches, including pulsed-field gel electrophoresis (PFGE) (27,28), PCR fingerprinting based on PCR ribotyping (11,37), rep-PCR (1,46), amplified fragment length polymorphism (AFLP) analysis (47), random amplified polymorphic DNA fragment (RAPD) analysis, and amplified rRNA gene restriction analysis (ARDRA) (42). While strain patterns derived using these methods distinguish strains from Rubus (subfamily Rosoideae) and other Spiraeoideae plants (1,37) and indicate a North American origin based on the slightly greater diversity of strains from this region (47), they provide poor discrimination of strains within local infested regions, which is required for effective implementation of phytosanitary control measures.…”
mentioning
confidence: 99%
“…Long-distance dispersal occurs principally via infected plant host material, limiting the number of invasion events into new regions. E. amylovora, even strains from the area of origin in North America (42), has been considered a genetically low-diversity species based on previous molecular approaches, including pulsed-field gel electrophoresis (PFGE) (27,28), PCR fingerprinting based on PCR ribotyping (11,37), rep-PCR (1,46), amplified fragment length polymorphism (AFLP) analysis (47), random amplified polymorphic DNA fragment (RAPD) analysis, and amplified rRNA gene restriction analysis (ARDRA) (42). While strain patterns derived using these methods distinguish strains from Rubus (subfamily Rosoideae) and other Spiraeoideae plants (1,37) and indicate a North American origin based on the slightly greater diversity of strains from this region (47), they provide poor discrimination of strains within local infested regions, which is required for effective implementation of phytosanitary control measures.…”
mentioning
confidence: 99%
“…Nevertheless, strains from Europe and the Mediterranean region can be distinguished by their PFGE pattern after XbaI restriction [18]. Further distinction was also possible by SSR analysis [3,21]. The usefulness of these and similar approaches, such as CRISPR sequences, may be limited by frequent changes due to random recombination within these DNA elements of the genome.…”
Section: Discussionmentioning
confidence: 99%
“…The final result is the number of repeat units that is calculated from the fragment size. In our laboratory, SSR analysis was used for typing of E. amylovora the etiologic agent of fire blight Barionovi et al, 2006). SSR typing data revealed that the spreading of fire blight from the western provinces to the east of Austria and onward to Hungary was only an apparently continuous event.…”
Section: Variable Number Of Tandem Repeat (Vntr) Analysismentioning
confidence: 99%